2013
DOI: 10.4103/2321-3868.113332
|View full text |Cite
|
Sign up to set email alerts
|

Burn blister fluids in the neovascularization stage of burn wound healing: A comparison between superficial and deep partial-thickness burn wounds

Abstract: Burn wound healing is a complex and dynamic process that involves the interaction between different cell types and mediators. Neovascularization is an imperative stage of wound healing and consists of not only angiogenesis but also adult vasculogenesis. A superficial partial-thickness burn (SPTB) heals within 2 weeks without scarring. A deep partial-thickness burn (DPTB), conversely, requires 2 weeks or longer to heal and requires an aggressive treatment to prevent hypertrophic scarring. Burn blisters on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
1
12
0
2
Order By: Relevance
“…Healing is expected within 2 weeks for SPTB and usually takes longer than 3 weeks for DPTB [10]. The periods of 12 and 17 days required, respectively, for complete reepithelialization of this patient’s wounds in the right upper limb and the left upper limb, suggest effectiveness of NTFS as a xenograft for the treatment of human burns.…”
Section: Discussionmentioning
confidence: 99%
“…Healing is expected within 2 weeks for SPTB and usually takes longer than 3 weeks for DPTB [10]. The periods of 12 and 17 days required, respectively, for complete reepithelialization of this patient’s wounds in the right upper limb and the left upper limb, suggest effectiveness of NTFS as a xenograft for the treatment of human burns.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, angiogenin has been demonstrated to be a key paracrine signaler in superficial and deep partial-thickness burns for the promotion of neovascularization. Pan et al demonstrated that angiogenin alone was able to induce CAC differentiation into ECs in the absence of VEGF-A, and that its absence was associated with a significant reduction in EC proliferation and new blood vessel formation in vivo [ 28 ].…”
Section: Reviewmentioning
confidence: 99%
“…[1] Chronic wounds can be very complex which implies that they have their own field of specialty within medicine. [2,3] Wounds are usually treated with wound dressings, which have strict requirements in order to realize optimal wound healing including biocompatibility, the ability to provide a moist environment while removing excess exudate, being nonadhesive and easily removable and processable in different sizes. [4,5] Nowadays, other important factors are considered during wound management.…”
Section: Introductionmentioning
confidence: 99%